Jobs and the labor force of tomorrow : migration, training, and education - Project Muse. (Urbana, IL : University of Illinois Press, 2017)
The new volume in the Urban Agenda series addresses the challenges shaping the development of human capital in metropolitan regions. The articles, products of the 2016 Urban Forum at the University of Illinois at Chicago, engage with the overarching idea that a dynamic metropolitan economy needs a diverse, trained, and available workforce that can adapt to the needs of commerce, industry, government, and the service sector. Authors explore provocative issues like the jobless recovery, migration and immigration, K12 education preparedness, the urban-oriented gig economy, postsecondary workforce training, and the recruitment and professional development of millennials.
Title Page; Copyright Page; Contents; Preface and Acknowledgments; Part One: Overview; "The Future of Work: Urban Economies in Transition"; Part Two: White Papers; "Human Capital in Context: Policies that Shape Urban U.S. Labor Markets"; "Immigration to the United States in the Post-Civil Rights Years"; "Toward Reframing the Open Door: Policy, Pedagogy, and Developmental Education in the Urban Community College"; "The Millennials"; Part Three: Synthesis; "9 to 5 to 0 and 1: The Future of Work"; List of Contributors
Description based on print version record.
Includes bibliographical references at the end of each chapters.
eBooks on EBSCOhost
Keywords: Labor market; Labor supply; Employment (Economic theory); Marché du travail; Emploi; employing; EDUCATION / Urban; Labor market; Labor supply